(untitled) (Quinto Sol, 2020)
This article analyzes the ways of obtaining and distributing the resources of the Liberal Party of Tucumán (conservative) from its creation, in 1917, until its dissolution, in 1930. To that end, it examines the role of sugar businessmen as party financiers, considering the weight of their contributions for electoral campaigns, as well as their impact on proselytizing practices and debates within the party. The text argues that the course of the Liberal Party reflected the difficulties, marches and counter-marches of the conservative leadership in confronting the complexity and increase in cost of the campaigns during the ampliation of democracy. The contributions of the sugar businessmen emerged, within this framework, as the predominant ways of financing, which had diverse implications within the party, as well as in its mechanisms of electoral proselytism and recruitment. The study of the methods of obtaining and distributing the resources advances on a marginal theme in the research on Argentine political parties during the analyzed stage.